Effects of eEF1A2 knockdown on autophagy in an MPP+-induced cellular model of Parkinson's disease. (March 2021) - Prommahom, Athinan; Dharmasaroja, Permphan
Highlights: eEF1A2 siRNA knockdown decreased LC3-II and phospho-Beclin-1 in MPP + -treated SH-SH5Y cells. eEF1A2 knockdown increased mitochondrial damage but reduced LC3-mitochodrial colocalization. eEF1A2 knockdown aggravated α-synuclein accumulation in MPP + -treated SH-SY5Y cells. eEF1A2 knockdown induced apoptosis in MPP + -treated SH-SY5Y cells through caspase-3 activation. eEF1A2 is essential for the survival of SH-SY5Y neuronal cells exposed to MPP + . Abstract: 1-Methyl-4-phenylpyridinium ion (MPP + ) is widely used to induce a cellular model of Parkinson's disease (PD) in dopaminergic cell lines. Downregulation of the protein translation elongation factor 1 alpha (eEF1A) has been reported in the brain tissue of PD patients. eEF1A2, an isoform of eEF1A, is associated with lysosome biogenesis that involves the autophagy process. However, the role of eEF1A2 on autophagic activity in PD has not been elucidated. In this work, we investigated the role of eEF1A2 on autophagy using eEF1A2 siRNA knockdown in differentiated SH-SY5Y neuronal cells treated with MPP + . We found that eEF1A2 was upregulated in differentiated cells, which could be silenced by eEF1A2 siRNA. Significantly, cells treated with MPP + after eEF1A2 knockdown showed a decreased number of LC3 puncta, decreased LC3-II/LC3-I ratio, and decreased phospho-Beclin-1, compared to the MPP + alone group. These cells showed extensive areas of mitochondria damage, with a reduction of mitochondrial membrane potential, but reduced mitophagy as indicated by the reduced colocalization of LC3 puncta with damaged mitochondria. Cells with eEF1A2 siRNA plus MPP + treatment aggravated α-synuclein accumulation but reduced colocalization with LC3. As a result, eEF1A2 knockdown decreased viability, increased apoptotic nuclei, increased caspase-3/7 activation and increased cleaved caspase-3 when cells were treated with MPP + . These results suggest that eEF1A2 is essential for dopaminergic neuron survival against MPP +, in part through autophagy regulation.